Effect of exposure frequencies of pear juice on tooth whitening - Munusamy, Gobalakrishna; Sukartini, Endang; Hayati, Ayu Trisna (Faculty of Dentistry Universitas Padjadjaran, 2013)
Introduction: Tooth whitening (Bleaching) is a method to restore discoloured teeth to the original tooth colour with a chemical process. The materials used in the bleaching process are hydrogen peroxide, sodium perborates and carbamide peroxide. Pear fruit consists of hydrogen peroxide which is potentially an oxidizing compound that produces free radicals that react with unsaturated bonding teeth staining substances. This study aims to analyzed tooth whitening effect of exposure of pear juice with different frequencies. Methods: The type of research was true in vitro experiment where samples of 32 maxillary premolar teeth had cut the root to CEJ. The specimens divided into four groups. The first group was soaked in pear juice two times, the second group three times, a third group four times, and the fourth was the control group using only mineral water. Tooth colour was measure using a Spectrophometer, conducted before and after individual soaking. Results: The research result is tested with ANOVA and Newman- Keuls Range Test showed a significant difference of tooth whitening degree between the frequency exposure pear juice after 2 times soaking, 3 times soaking and 4 times soaking. Conclusion: There are difference degree of whitening from the difference frequency exposure of pear juice and Pear juice exposure of 4 times gives higher whitening effect compared to frequency of 3 times, 2 times and control group which is soaked in water.